Factors influencing customer loyalty towards fast food restaurants in Malaysia : an empirical study - Al Masud, Md Abdullah (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
Customer loyalty has become a critical and key focal point for any business organization as the competition level is highly fierce. Therefore, every organization should concentrate on gaining customer loyalty in order to increase profits and maintain sustainability in the business market. Any successful organization should satisfy their customers in order to achieve their trust and maintain good relationships with them. This could change regular customers into loyal ones which ensure the continuing progress of the business. The main objective of this study is to increase the understanding in the relationships between customer loyalty and some of the factors of loyalty that could directly contribute to loyalty towards fast food restaurants in Malaysia. Convenience sampling method was used to collect quantitative data from 250 customers of fast food restaurants in Kuala Lumpur, Malaysia and was later analyzed using the correlation and regression technique of SPSS. The study reveals that customer loyalty is associated with the quality of product, restaurants environment, convenience and price and value towards fast food businesses in Malaysia. Among all the factors convenience and quality of food have significant and positive influence on customer loyalty. Future study on this topic needs to be conducted by using a bigger combination of independent variables with a more comprehensive model and the analysis need to further be expended and carried out using factor analysis. This would contribute additional findings that would produce enhanced understanding on the issues and benefit the business in formulating future marketing and customer relationship strategies.